The Impact of Climate Change on Operational Probable Maximum Precipitation Estimates. Issue 11 (17th November 2022) - Visser, J. B.; Kim, S.; Wasko, C.; Nathan, R.; Sharma, A.
Abstract: The safety of high‐risk water infrastructure, such as dams and nuclear power plants, is often assessed by reference to their ability to accommodate floods derived from the Probable Maximum Precipitation (PMP). However, a key shortcoming of traditional PMP estimates is the assumption of a stationary climate, with evidence indicating that key meteorological conditions related to the magnitudes of extreme storms, such as atmospheric moisture, are changing in a warming climate. Due to the pragmatic nature of PMP methods derived for design purposes, inferring potential changes in PMP estimates based solely on trends or projections of atmospheric variables can ignore PMP method complexities and constraints. Here we explore how different traditional PMP methods will respond to a potential increase in atmospheric moisture. We find that increases in persisting dewpoint will lead to increases in PMP estimates, and the nature of this impact depends on whether the moisture maximization step is based on local or transposed regional information. An historical trend analysis reveals annual maximum persisting dewpoint temperatures have increased continuously over Australia over the past 60 years, with further increases predicted over the coming decades for all Shared Socioeconomic Pathways (SSPs). PMP estimates across Australia are predicated to increase by an average value of 13% by 2100 based on the conservative SSP1‐2.6, compared to 33% for SSP5‐8.5. We conclude PMP methods will require regular updating to account for changing persisting dewpoints and likely progressive increases in PMP, and the ensuing flood estimates. Key Points: The assumption of a fixed Probable Maximum Precipitation (PMP) is incompatible with historical increases in atmospheric moisture PMP estimates are expected to increase between 13% and 33% on average across Australia by 2100 Operational PMP estimates for 546 large dams across Australia are expected to increase between 14.5% and 38% on average